The Indonesian Career Literacy Scale: The Early-Stage Development and Validity of the Indicators - Widyowati, Arini; Widiana, Herlina Siwi (Journal of Educational, Health and Community Psychology, 2024)
Career literacy is an important factor that supports individuals in setting career goals and making career decisions. To assess the level of individuals’ career literacy, a valid measurement that can describe the true literacy level is needed. However, so far there are no tools to assess career literacy levels among adolescents in Indonesia. The study aims to validate the behavioural indicators of a career literacy scale for Indonesian adolescents. The research involved five experts in career development and psychometry. The data collected through the questionnaire contains 50 behavioural indicators of the career literacy scale that was analyzed through V Aiken’s formula. The results revealed that all indicator have V coefficient ranging from 0.40 – 1.00. The 24 selected indicators consist of three indicators in each aspect of the concepts dimension and five indicators in each aspect of the skills dimension as the indicators of the Indonesian Career Literacy Scale. Therefore, the career literacy construct identified in a study in USA is also relevant for Indonesians and can be used in developing the Indonesian Career Literacy Scale.